Pengukuran Untuk Mendeteksi Deformasi Bangunan Sipil - Kahar, Sutomo (Department of Civil Engineering, Diponegoro University, 2006)
Deformation for territory will impact to above the building stability and also will give an impact to the coordinate points as a control the building. The problem will are begin from decided the points as a reference points in the measurement after deformation, because all of the reference points are arguing the truth as a control points. Therefore, the truth of control points in the long term need to watching the various deformations or changing above the land.Keywords: deformation, control point arguing, measurement systemPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3937[How to cite: Kahar, S., 2006, Pengukuran Untuk Mendeteksi Deformasi Bangunan Sipil, Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 1, pp. 78-84]